Functional food addressing heart health: do we have to target the gut microbiota?. Issue 6 (November 2015) - Ryan, Paul M.; Ross, Reynolds Paul; Fitzgerald, Gerald F.; Caplice, Noel M.; Stanton, Catherine
Abstract : Purpose of review: Health promoting functional food ingredients for cardiovascular health are generally aimed at modulating lipid metabolism in consumers. However, significant advances have furthered our understanding of the mechanisms involved in development, progression, and treatment of cardiovascular disease. In parallel, a central role of the gut microbiota, both in accelerating and attenuating cardiovascular disease, has emerged. Recent findings: Modulation of the gut microbiota, by use of prebiotics and probiotics, has recently shown promise in cardiovascular disease prevention. Certain prebiotics can promote a short chain fatty acid profile that alters hormone secretion and attenuates cholesterol synthesis, whereas bile salt hydrolase and exopolysaccharide-producing probiotics have been shown to actively correct hypercholesterolemia. Furthermore, specific microbial genera have been identified as potential cardiovascular disease risk factors. This effect is attributed to the ability of certain members of the gut microbiota to convert dietary quaternary amines to trimethylamine, the primary substrate of the putatively atherosclerosis-promoting compound trimethylamine- N -oxide. In this respect, current research is indicating trimethylamine-depleting Achaea – termed Archeabiotics as a potential novel dietary strategy for promoting heart health. Summary: The microbiota offers a modifiable target, which has the potential to progress or prevent cardiovascular disease development. Whereas host-targeted interventions remain the standard, current research implicates microbiota-mediated therapies as an effective means of modulating cardiovascular health.